PEER COUNSELOR: ONLINE PFA (PSYCHOLOGICAL FIRST AID) DURING COVID-19 PANDEMIC - Eka Widiasari; Henie Kurniawati; Zahratika Zalafi (Proyeksi: Jurnal Psikologi, 2022)
Covid-19 had a global impact on almost all aspects of life, including mental health. The application of social distancing and quarantine methods as an effort to control the spread of Covid-19 has changed the way we socialize, even disrupting mental health. With this change, mental health services are also affected where the service mechanism that was previously carried out face-to-face has changed to online services. Tele PFA is a relevant alternative as a mental health service solution during a pandemic. At the Psychology and Career Development Service Center (P4K) of UIN Prof. KH. Saifuddin Zuhri (UIN SAIZU) Purwokerto, PC is at the forefront of PFA services for students and public. PCare the senior students of Counseling Department at Dakwah Faculty that join P4K through selection and PFA training. Tele PFA was chosen because it can be done by anyone who is trained and has knowledge of how to do PFA through various online methods. The purpose of this study was to obtain a descriptive idea of Tele PFA services dynamics. This study focuses on Tele PFA services carried out by PCs who are members of the P4K UIN SAIZU. Research data collected using Focus Group Discussion (FGD) that was conducted online with 17 PC respondents. FGD results showed that the complaints submitted by clients are generally related to education, family and love matters. The result concluded that the most requested method for Tele PFA were made through chat, followed by services via voice calls, voice notes and video calls. Challenges experienced by PCs when performing network-related services, unfavorable environmental conditions during service and countertransference. The PFA tele service is very helpful in alleviating client problems and also increasing PC self-development, especially related to counseling skills.